2022
DOI: 10.1088/1755-1315/973/1/012004
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Ion-Exchange Resins and Granular Activated Carbon with the Sonochemical Technique for Enabling Adsorption of Aqueous Per- and Polyfluoroalkyl Substances

Abstract: Regeneration of adsorbents for reuse is crucial for reducing operating costs and maintaining sustainable systems. Few researchers have studied the regeneration of sorbents without using chemical solvents or appropriate methods. The purpose of this study was to evaluate the feasibility of the sonochemical technique (ST) for the regeneration of granular activated carbon (GAC), a mixed cation and anion resin (DOWEX MB-50), and an anion resin (IRA910) for the removal of per- and polyfluoroalkyl substances (PFAS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Previous research has investigated spent adsorbents using the sonochemical technique (ST), which does not include the use of chemical reagents and is environmentally friendly. Their findings suggested that the ST is a successful way to produce adsorbents for PFAS adsorbed in water (Sukeesan et al, 2022). Finally, the importance of adsorption performance and adsorbent regeneration for sustainable treatment systems could be used to consider adsorbent selection for PFAS that are otherwise particularly difficult to treat.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has investigated spent adsorbents using the sonochemical technique (ST), which does not include the use of chemical reagents and is environmentally friendly. Their findings suggested that the ST is a successful way to produce adsorbents for PFAS adsorbed in water (Sukeesan et al, 2022). Finally, the importance of adsorption performance and adsorbent regeneration for sustainable treatment systems could be used to consider adsorbent selection for PFAS that are otherwise particularly difficult to treat.…”
Section: Resultsmentioning
confidence: 99%
“…The oxygen atom contained in the head structure of the PFAS may serve as an acceptor and bond with the hydrogen atom (He et al, 2013;Lu et al, 2016), suggesting that particle size distribution, resin functional groups, PFAS molecules, and hydrophobic interactions during the adsorption process play a key role in explaining the kinetics of PFAS. Their findings suggested that the ST is a successful way to produce adsorbents for PFAS adsorbed in water (Sukeesan et al, 2022).…”
Section: Adsorption Removal Of Pfasmentioning
confidence: 99%
“…Regenerating and disposing of used resins are among the main downsides of ion exchange resins for PFAS removal. Studies reveal that regenerated resins are less efficient in adsorbing PFAS and require a longer contact time than single-use resins [ 31 , 40 , 67 ]. Furthermore, the chemical regeneration process of the resins is expensive; therefore, the destruction of resins is a better option to avoid the loss [ 68 , 69 ].…”
Section: Current Treatment Approachesmentioning
confidence: 99%